(untitled) (Philology, 2026)
The article outlines the influence of the West Germanic languages spoken on the territory of today’s Germany and the Netherlands on the continental Scandinavian languages, Danish, Norwegian and Swedish, during the Middle Ages, focusing on the considerable impact of Middle Low German during the time of the Hanseatic League (14th to 15th century). The paper discusses the various theories related to the type of language contact and provides examples to illustrate the German influence on the Scandinavian languages at the vocabulary level of lexis.